Hybrid Make-to-Stock and Make-to-Order (MTS-MTO)Scheduling Model in Multi-Product Production System - Kusuma, Purba Daru (International Journal of Integrated Engineering, 2022)
In production process, scheduling plays important role in meeting the orders and reducing the cost. This process becomes more complicated when the factory produces various products. Scheduling model in production process can be divided into two groups: make-to-stock (MTS) and make-to-order (MTO). General constraint in make-to-stock model is limited production capacity and inventory cost. This work aims to propose hybrid MTS-MTO model that can improve lead time and maintain low inventory. In this work, we propose three hybrid MTS-MTO scheduling models production system that produces multiple products. In these models, we modify several scheduling algorithms that are used in computer system, such as: shortest remaining time, shortest processing time, and Round Robin. These models are hybrid base stock-FCFS model, hybrid base stock-modified shortest processing time model, and modified base stock-shortest remaining time model. This model then is implemented into production simulation. In this simulation process, we compare the proposed models with the existing base stock model. Based on the simulation result, these proposed models perform better than the basic MTS model. The hybrid base stock-modified shortest processing time model performs as the best model in creating high completion ratio, low lead time, and low inventory ratio. In certain condition, our proposed model performs 344 percent in completion ratio, 19.8 percent in lead time, and 3 percent in inventory ratio compared with the existing model.